2020
DOI: 10.1002/joe.21997
|View full text |Cite
|
Sign up to set email alerts
|

The role of organizational culture in knowledge sharing and transfer in Pakistani banks: A qualitative study

Abstract: To identify the elements of organizational culture that support or act as a barrier to corporate knowledge creation, sharing, and transfer, researchers conducted semi‐structured interviews with 16 top‐level managers in five banks based in Karachi, Pakistan. The findings reveal that encouraging the exchange of ideas among employees through social interactions in the workplace facilitates the transfer of tacit knowledge. The inability to adapt to new technology, a lack of awareness of the benefits of effective k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 33 publications
0
26
0
2
Order By: Relevance
“…For their part, Brown and Frame [62] identified collaboration as the mechanism through which organizational culture facilitates knowledge sharing. In the same direction, Memon et al [63] reported a relationship between an organizational culture that encourages its workers and the sharing of tacit knowledge. Jarrah et al [64] supported the hypothesis that knowledge sharing mediates the relationship between a culture based on obedience and organizational performance.…”
Section: Knowledge Sharing and Culturementioning
confidence: 96%
“…For their part, Brown and Frame [62] identified collaboration as the mechanism through which organizational culture facilitates knowledge sharing. In the same direction, Memon et al [63] reported a relationship between an organizational culture that encourages its workers and the sharing of tacit knowledge. Jarrah et al [64] supported the hypothesis that knowledge sharing mediates the relationship between a culture based on obedience and organizational performance.…”
Section: Knowledge Sharing and Culturementioning
confidence: 96%
“…Rahman, Hussain and Haque (2011) collected evidence from the thriving textile sector in Bangladesh about the hazardous effects of organizational politics, lobbying and group interests that superseded the organizational interests with objectives, which not only endangered employees' performance but proved detrimental to organizational long-haul sustainable competitiveness. Memon, Qureshi, and Jokhio (2020) investigated organizational culture in nexus with knowledge management and emphasized on the role of knowledge preserving, sharing, and transfer for the success and sustainable development of organizations. Rao (2016) emphasized on the role of culture in the context of success of family businesses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Memon et al. (2020) investigated organizational culture in nexus with knowledge management and emphasize the role of knowledge in preserving, sharing, and transferring in the success and sustainable development of organizations. Rao (2016) emphasizes on the role of culture in the context of success of family businesses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…That leads the discussion towards the role played by universities in the creation of entrepreneurs and entrepreneurship as a whole as the current age entrepreneurs are more in number having university education than non-university educators quite different from the past entrepreneurship trend (Altantsetseg, Chen, & Chang, 2017;Ferreira & Trusko, 2018). Hence, the formal role of universities as to provide fundamental knowledge, create the knowledge, disseminate the knowledge has been added by the commercialization of the knowledge as well (Memon, Qureshi, & Jokhio, 2020). Thus, the universities today have become the entrepreneurial commercial base or entrepreneurial universities as suggested by the triple-helix model that it is quite important that, universities, government and industry work together in the knowledge-economy in order to achieve the greatest good of all (Cvijić, Tatarski, Katić, Vekić, & Borocki, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%